Effectiveness of TTD and MMS Supplementation in Preventing Anemia in Pregnant Women in the Working Area of the Moncongloe Community Health Center, Maros Regency - Subair, Hardyanty; Erni Moilis (Asosiasi Dosen Muda Indonesia, 2025)
Nutritional problems in pregnant women remain a major challenge in Indonesia. One of the most serious problems is anemia due to iron deficiency. According to the 2018 Riskesdas results, nearly half of pregnant women in Indonesia experience this condition. Anemia can cause various problems, such as premature birth, low birth weight, and even maternal death. The purpose of this study was to determine the comparative effectiveness of Iron Supplement Tablets (TTD) and Multiple Micronutrient Supplements (MMS) in increasing hemoglobin (Hb) levels in pregnant women. Research method This study was a quantitative observational study with a cross-sectional approach. The research design used a comparative approach, namely by comparing hemoglobin levels in pregnant women who consumed Iron Supplement Tablets (TTD) and those who consumed Multiple Micronutrient Supplements (MMS) in the first and third trimesters.The results showed that hemoglobin levels in pregnant women who consumed Multiple Micronutrient Supplement (MMS) were higher than those in the group who consumed Iron Supplement Tablets (TTD). This difference can be explained based on the nutritional content of each supplement. In conclusion, the administration of multiple micronutrient supplements (MMS) proved to be more effective in increasing hemoglobin levels in pregnant women than administering iron tablets (TTD) alone.